Caracterización de los componentes forrajeros de cuatro asociaciones gramíneas/ Arachis pintoi - Sánchez Gonzáles, Jorge (Universidad de Costa Rica, 2013)
The association of the herbaceous legume Arachis pintoi CIAT 17434with tropical grasses has a great potential to improve cattle production in grazing systems. This study was conducted to characterize the nutritional quality of these associations and to obtain useful information to improve the feeding strategies for cattle in the humid tropics of Costa Rica. The experiment was carried out at the La Balsa farm of the lnstituto Tecnológico de Costa Rica, located in an area classified as Humid Tropic. Annual average rainfall in the zone is 3062 mm and average temperature is 26,7 C. Eight treatments conformed as a factorial arrangement of four grass/Arachis pintoi CINI 17494 associations and two stocking rates (3,0 and 1,5 A.U.) were evaluated. Grasses under evaluation were Cynodon nlemfuensis, Brachiaria dictyoneura CIAT 6133, Brachiaria brizantha CIAT 6780 and Brachiaria brizantha CIAT 664. Paddocks were grazed every 35 ciays for 5 to 7 days. Composed samples were taken at each grazing cycle and they were analysed for Crude Protein (AOAC 19g4, Neutral Detergent Fiber and Lignin (Van Soest y Robertson 1984), Non-Fiber Carbohydrates (Van Soest et al. 1991). Total Digestible Nutrients were estimated by the model developed by Weiss et al. (7992) and the Digestible and Metabilizable Energy contents by standard NRC (1989) procedures. Crude Protein content was higher (P<0.05) for Arachis pintoi than for the grasses evaluated (average levels were 79.4 and7.8/" respectively). Mean Neutral Detergent Fiber levels in grasses were 73.5: meanwhile in Arachis pintoi were 57.9"/", these values were significantly different (P<0.05 Lignin content was higher (P<0.05) in Arachis pintoi than in the grasses with which this legume was associated, mean values were 10.6 and 6.5% respectively. Arachis pintoi showed a mean value of Non-Fiber Carbohydrates of 28.9% which was significantly (P<0.05) higher than the level of 11.4% obtain for the grasses. Energy levels were higher (P<0.05) in the legume than in the grasses. Total Digestible Nutrients were 51.1 and 48.7%. Digestible Energy 2.25 and 2.15 Mcal/kg of DM. Metabolizable Energy 1.83 and 1.72 Mcal/kg of DM for Arachis pintoi and for the grasses with which the legume was associated, respectively, Arachis pintoi increases Crude Protein. Non-Fiber Carbohydrates and Energy contents of the legumegrass associations. This has important implications for cattle production based on grazing, since these are the most limiting nutrients in production systems based on tropical pastures.